PENGARUH PEMAHAMAN PAJAK, KUALITAS PELAYANAN DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK (Studi Empiris Pada WP OP yang Melakukan Kegiatan Usaha di KPP Pratama Semarang Candisari) - Roy Purnaditya, Riano; Rohman, Abdul (Diponegoro Journal of Accounting, 2015)
This study as a purpose to analyze the influence of the understanding of taxpayers, quality of service, and tax penalties on tax compliance. Attribution theory explains that the internal effect caused by an individual's personal conduct which is the understanding of taxpayers on tax compliance, while external influences are thought to result from an outside party that is in terms of quality of service tax authorities and tax penalties provided by the government. Based on social learning theory proposed by Albert Bandura (1977), this theory should conduct direct observation and experience to participate in terms of tax compliance.Respondents in this study is an individual taxpayer who carries on business in Semarang Candisari STO. The analysis technique used is the technique of multiple regression analysis with the data obtained using quantitative methods are surveys using a questionnaire to the media which is convenience sampling technique. Total number of questionnaires were analyzed by 114 questionnaires.This study shows that the understanding of tax, service quality and the tax authorities, and the sanctions applicable taxes and significant positive effect on tax compliance.